Engaging natural killer cells for cancer therapy via NKG2D, CD16A and other receptors - Kerry A. Whalen; Kavya Rakhra; Naveen K. Mehta; Alexander Steinle; Jennifer S. Michaelson; Patrick A. Baeuerle (Taylor & Francis Group, 2023)
ABSTRACTThe field of immuno-oncology has revolutionized cancer patient care and improved survival and quality of life for patients. Much of the focus in the field has been on exploiting the power of the adaptive immune response through therapeutic targeting of T cells. While these approaches have markedly advanced the field, some challenges remain, and the clinical benefit of T cell therapies does not extend to all patients or tumor indications. Alternative strategies, such as engaging the innate immune system, have become an intense area of focus in the field. In particular, the engagement of natural killer (NK) cells as potent effectors of the innate immune response has emerged as a promising modality in immunotherapy. Here, we review therapeutic approaches for selective engagement of NK cells for cancer therapy, with a particular focus on targeting the key activating receptors NK Group 2D (NKG2D) and cluster of differentiation 16A (CD16A).